MOTIVASI SISWA DALAM BELAJAR MENGGUNAKAN METODE EDUCATION GAMES PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN 001 TELUK MERBAU KECAMATAN KUBU KABUPATEN ROKAN HILIR - M. Nur (Jurnal Payung Sekaki : Kajian Keislaman, 2025)
This research is motivated by the problem of low student motivation in learning using the education games method in learning Islamic Religious Education at SDN 001 Teluk Merbau, Kubu District, Rokan Hilir Regency. This research is in the form of data analysis techniques, namely qualitative descriptive techniques. The purpose of this study was to determine how to foster student motivation in learning and factors that influence student motivation in learning using the education games method in learning Islamic Religious Education at SDN 001 Teluk Merbau, Kubu District, Rokan Hilir Regency. This research uses qualitative descriptive method. Based on the data obtained, it can be concluded that student motivation in learning using the education games method in learning Islamic Religious Education at SDN 001 Teluk Merbau, Kubu District, Rokan Hilir Regency is quantitatively 56.1% between 56% - 75%, so it is included in the “GOOD” category.